ORGANIZATIONAL AND LEGAL BASIS OF PREPARING ATHLETES FOR INTERNATIONAL COMPETITIONS - Khanturaev, Nodir; Ochilova, Baxti (Научно-просветительский журнал "Наставник", 2020)
This article covers the development and popularization of physical education and sports so as to promote a healthy lifestyle among young people, educate a harmoniously developed generation, as well as create an organizational basis for preparing young people for international competitions.